2014
DOI: 10.3892/ijmm.2014.1649
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic analyses of the histamine H1 receptor and its role in cancer prediction

Abstract: Abstract. The human histamine receptor H1 (HRH1) gene is located on chromosome 3p25 and encodes for a 487 amino acid G protein-coupled receptor (GPCR) with a long third intracellular loop (IL3). The HRH1 predominantly couples to Gα q/11 proteins, leading to the activation of phospholipase C (PLC) and subsequent release of the second messengers inositol trisphosphate (IP 3 ) and diacylglycerol (DAG) followed by the activation of PKC and the release of [Ca 2+ ] i . In the present study, we identified HRH1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
(45 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, Our results from TCGA-based survival analysis indicated that overexpressed H1HR predicted a poor survival only in HCC patients with high CD68 expression levels, but not in HCC patients with low CD68 expression levels, which further suggested that increased infiltration of myeloid may aggravate the oncogenic effects exerted by H1HR in HCC. However, the relationship between the expression of H1HR and prognosis varied in different cancers, even in the same cancer from different databases [23]. This may be explained by the fact that the function of H1HR in different tumor types may be multidimensional, and it may not simply function as just an oncogene or tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Our results from TCGA-based survival analysis indicated that overexpressed H1HR predicted a poor survival only in HCC patients with high CD68 expression levels, but not in HCC patients with low CD68 expression levels, which further suggested that increased infiltration of myeloid may aggravate the oncogenic effects exerted by H1HR in HCC. However, the relationship between the expression of H1HR and prognosis varied in different cancers, even in the same cancer from different databases [23]. This may be explained by the fact that the function of H1HR in different tumor types may be multidimensional, and it may not simply function as just an oncogene or tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…The RNPC1 gene and amino acid sequences were selected from the Ensembl database (http://www.ensembl.org/index.html), based on orthologous and paralogous associations. The selected RNPC1 sequences were applied as queries in order to search for the RNPC1 gene using the BLAST tool at the National Center for Biotechnology Information (NCBI), in order to confirm whether their best hit was an RNPC1 gene (27)(28)(29)(30)(31)(32)(33). The number, length and structure of the exons and introns in the RNPC1 gene in all species were collected from Ensembl.…”
Section: Methodsmentioning
confidence: 99%
“…ncbi.nlm.nih.gov/Blast.cgi) (15)(16)(17)(18). Conserved transcription factor-binding sites in the promoter regions of the human WTAP gene were identified from the SABiosciences' proprietary database, DECODE (Qiagen, Inc., Valencia, CA, USA), which combines text mining with the University of California, Santa Cruz genome browser data (19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
“…The functionally relevant SNPs of the human WTAP gene were extracted from the Ensembl genome databases and the Short Genetic Variations database (ncbi.nlm.nih.gov/snp), as previously described (15)(16)(17)(18)(19)(20)(21). The SNPs causing missense mutations were then identified.…”
Section: Identification Of Functionally Relevant Snps In the Human Wtmentioning
confidence: 99%